Sports coaching research context consequences and consciousness - Bush, Anthony (Routledge research in sport culture and society, 2012)
This book is respone to the growing consensus that sports coaching research need to extend its physical and intellectual boundries. Indeed despite considerable reearch from a number of theoritical and empirical perspective.